The divide of consonant of open mouth syllable in the Mandarin in the end of Qing Era and modern dialect. - Wong, Ling Yann (2011)
This paper mainly investigates the divide of the consonant of the Ying(影) and Yi (疑) consonants of open mouth syllables（开口呼）from the middle ancient period in the Mandarin dialects in the end of Qing era, and towards its development in the modern dialects. The Yingand Yi consonants of the open mouth syllables which noted by westerners in their Romanized Mandarin texts have three different written forms, the first is written as a consonant of [?-] , the second is written as a consonant of [ɡ-] and the last form has been changed to zero consonant. This study finds that the Mandarin dialects which originated from different characteristics of sound systems have different written forms for the consonants of open mouth syllables. Based on the dialects from the Mandarin territories, the development of the consonants of open mouth syllables basically still remained the different written forms from the end of Qing era for these consonants in the Mandarin dialects from different territories, the consonants of open mouth syllables still remain as zero consonants in Beijing and Nanjing modern dialects, but normally have been changed to the consonant of [?-] in the Chengdu modern dialect currently.